Complexity Boundaries for Horn Description Logics. - Krötzsch, M; Rudolph, S; Hitzler, P (AAAI Press, 2007)
Horn description logics (Horn-DLs) have recently started to attract attention due to the fact that their (worst-case) data complexities are in general lower than their overall (i.e. combined) complexities, which makes them attractive for reasoning with large ABoxes. However, the natural question whether Horn-DLs also provide advantages for TBox reasoning has hardly been addressed so far. In this paper, we therefore provide a thorough and comprehensive analysis of the combined complexities of Horn-DLs. While the combined complexity for many Horn-DLs turns out to be the same as for their non-Horn counterparts, we identify subboolean DLs where Hornness simplifies reasoning. Copyright ©2007, Association for the Advancement of Artificial Intelligence (www.aaai.org). All rights reserved.